SMEs and Halal certification. - Abdul, Mohani; Ismail, Hashanah; Hashim, Haslina; Johari, Juliana (David Publishing Company, 2009)
This paper reports on a survey of SMEs and their perception towards Halal certification. Based on 136 SMEs which participated in the study, only 64.9 percent of these SMEs have obtained Halal certification and 44.3 percent of these entrepreneurs are Muslims. A test of association between religion and certification was found to be significant. Although more than 60 percent have ventured internationally, there is no significant association between Halal certification and venturing internationally. Among those that have obtained Halal certification, only 50.7 percent agree that Malaysia has a proper monitoring mechanism on Halal certification compliance and only 38.2 percent of them agree that information on Halal hub in Malaysia is sufficient. This is an implementation gap which needs to be addressed.